Atypical cinical manifestation of leprosy in Indonesian male adolescent: a case report - Dion Darius Samsudin; Mulya Rahma Karyanti (Indonesian Pediatric Society, 2021)
Leprosy, also known as Hansen’s disease, is a chronic infectious disease with high prevalence, but often neglected in Indonesia. Indonesia ranks the 3rd worldwide, after India and Brazil, with 17,439 new cases reported in 2019.1 This disease is caused by Mycobacterium leprae, an acid-fast, rod-shaped bacillus, which mainly affects the skin, peripheral nerves, upper respiratory tract mucosa, and eyes. Early diagnosis of the disease is fundamental, because delayed treatment may lead to severe deformities and disabilities.2 The current multidrug treatment (MDT) for leprosy is widely available in Indonesia for free. According to the World Health Organization (WHO),1 leprosy is one of 20 diseases recognised as neglected tropical diseases (NTDs), a group of disease which present significant burden amongst the poorest, often unheard communities. Eradication of leprosy is challenging because of the difficulty in diagnosis, as leprosy imitates various diseases, as well as treatment delay, high transmission, and social stigma. The regions of highest leprosy prevalence in Indonesia are in Java, Sulawesi, Maluku, and Papua.3,4 Among 17,439 new cases in 2019, 1,861 (10%) were children under 15 years of age.1 The detection of new cases in children indicates high transmission, and lack of mechanisms to control endemic infections.2 The aim of this report is to share our experience in diagnosing advanced stage leprosy with atypical clinical characteristics in a male adolescent.